Skeletal Muscle Metastases to the Flexor Digitorum Superficialis and Profundus from Urothelial Cell Carcinoma and Review of the Literature - Marco Guidi; Cesare Fusetti; Stefano Lucchina (Case Reports in Urology)
Urothelial cell carcinoma (UCC) metastases to skeletal muscle are extremely rare and usually found in patients with advanced stage cancer. The most common sites of bladder cancer metastases are lymph nodes, lung, liver, and bones. Muscle is an unusual site of metastases from a distant primary cancer, due to several protective factors. We present a rare case of 76-year-old patient with metastases in the flexor digitorum superficialis (FDS) and flexor digitorum profundus (FDP) muscles, 2 years after a radical cystectomy for invasive UCC of the bladder. This case is the first description of a forearm lesion, with an extensive infiltration of the volar compartments of the forearm, and the first one with a clear functional impairment.